Assessment of the Effectiveness of Health Education and Screening Test in Reducing Multiple Myeloma in the Middle-Elderly Nigerians – A Study Proposal Methodology - Nwabuko, Ogbonna; John, Raphael Edoka (British Journal of Healthcare and Medical Research, 2022)
The developing countries including African union bear the highest global burden of cancer. Despite the increase, there is a huge gap on data management and case ascertainment of majority of these cancer diseases. This could be as a result of inability of the national cancer control agencies of most African union member countries to activate the priority areas of actions on cancer prevention. One of the malignant haematological diseases under-diagnosed in Nigeria is multiple myeloma. It causes end-stage organ failure including renal myeloma. This study proposal is a methodological overview of the strategic ways of assessing the impact of public health education and screening test in reducing the burden of multiple myeloma in Nigeria. Two pairs of keywords (screening test and multiple myeloma), and (health education and multiple myeloma) were used as search strategy to identify the Problem, Intervention, Comparison, and Outcome (PICO) elements of the research question. PubMed, MedLine, Google Scholar, African Journal Online (AJOL), Cumulative Index Nursing and Allied Health Literature (CINAHL) were the database reviewed. This paper presented a synthesis of the reviewed articles and the expected outcomes of possible interventions on the burden of multiple myeloma disease in Nigeria. The study report was analysed and grouped according to the following categories: PICO research question on multiple myeloma, rationale for the study, study objective, study design, methodology, ethical considerations, data management and dissemination. Conclusion: This methodological study will serve as a public health safety measure for reducing the burden of multiple myeloma in Nigeria. The hallmark of the study outcome may be useful in crafting the surveillance epidemiological end-result (SEER) cancer statistics research database for multiple myeloma in Nigeria.